Effect of PSBB Policy on Stock Prices and Trading Volume of JCI Activity (Before and During PSBB Volume 2) - Parulian; Muhamad Syahwildan (Journal of Business, Management, & Accounting, 2021)
This study examines an event study, regarding the difference in the JCI stock price and trading volume activity (TVA) in events before and during the PSBB policy volume 2. Secondary data comes from the pre-opening session (pre-opening) of stock trading on the stock exchange on 27 July -11 Nov 2020. The research sample taken is the JCI. This study uses the Wilcoxon signed rank test analysis. The results showed that the average stock price in the events before and during the PSBB policy volume 2 there was a difference in the JCI stock price, while the results from the trading volume activity (TVA) test showed that there was no difference in the average trading volume before and during incident. Based on the results of these tests, it is indicated that PSBB volume 2 is a negative and positive sentiment that caused a reaction to stock transactions causing this event to make investors worried even though trading volume increased.